2014
DOI: 10.4067/s0718-381x2014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Use of Documentation in Identification of a Skeletonized Body in Legal Dental Practice

Abstract: The analysis of dental records is an essential tool for human identification. The present study aimed to highlight the importance of dental records for identification of skeletonized bodies. In form of conclusion, the method of dental identification using dental records represents a valid option for forensic dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Sin embargo, en situaciones reales cabe esperar que las alteraciones radiculares acontezcan algo más tarde puesto que la protección de los tejidos de alrededor no ha sido considerada en este trabajo de investigación. Cabe destacar que es la corona dental la que más a menudo proporciona información con interés forense (Terada et al, 2014).…”
Section: Discussionunclassified
“…Sin embargo, en situaciones reales cabe esperar que las alteraciones radiculares acontezcan algo más tarde puesto que la protección de los tejidos de alrededor no ha sido considerada en este trabajo de investigación. Cabe destacar que es la corona dental la que más a menudo proporciona información con interés forense (Terada et al, 2014).…”
Section: Discussionunclassified
“…However, orthodontic records became more prevalent over the last years in the routine of dental human identification due to the popularization and accessibility to orthodontics treatment. As consequence, the intraoral photographs used to register therapeutics before, during and after the orthodontic treatment became more often part of the AM data available in Forensic Dentistry (PARANHOS et al, 2008;SILVA et al, 2011;TERADA et al, 2014). In the present study the case reported was founded on orthodontic records produced during the treatment, which enabled the analysis of the permanent teeth through intraoral photographs and a panoramic radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…The family who searched for a missing portion was called and asked about the orthodontic records. Finally this person was identified [21].…”
Section: Example Of a Case Held By An Orthodontist As A Forensic Expertmentioning
confidence: 99%